81.1k views
2 votes
Factorize py+ pz + y² + yz​

2 Answers

5 votes

Answer:

you could either say p(y+z)+y(y+z)or y(p+y)+ z(p+y)

Explanation:

I cant really explain it but I hope this helps

User Parham
by
5.3k points
1 vote

Answer:
(p+y)(y + z) \\\\

=======================================

Work Shown:


py + pz + y^2 + yz \\\\(py + pz) + (y^2 + yz) \\\\p(y + z) + (y*y + yz) \\\\p(y + z) + y(y + z) \\\\(p+y)(y + z) \\\\

I grouped the terms into pairs. Then I factored the GCF from each pair

The GCF of py+pz is p

The GCF of y^2+yz is y

On the last line, I factored out the overall GCF (y+z)

You can use the FOIL rule or the distributive property to expand out (p+y)(y+z) and you should get the original expression back again. This is a way to confirm the correct answer.

User Jimmy Z
by
5.2k points